Chiral Carbon Dots Mimicking Topoisomerase I To Mediate the Topological Rearrangement of Supercoiled DNA Enantioselectively. (28th April 2020) - Li, Feng; Li, Shuai; Guo, Xiaocui; Dong, Yuhang; Yao, Chi; Liu, Yangping; Song, Yuguang; Tan, Xiaoli; Gao, Lizeng; Yang, Dayong
Abstract: Nanomaterials with enzyme‐mimetic activities are possible alternatives to natural enzymes. Mimicking enzymatic enantioselectivity remains a great challenge. Herein, we report that cysteine‐derived chiral carbon dots (CDs) can mimic topoisomerase I to mediate topological rearrangement of supercoiled DNA enantioselectively. d ‐CDs can more effectively catalyze the topological transition of plasmid DNA from supercoiled to nicked open‐circular configuration than l ‐CDs. Experiments suggest the underlying mechanism: d ‐CDs intercalatively bind with DNA double helix more strongly than l ‐CDs; the intercalative CDs can catalyze the production of hydroxyl radicals to cleave phosphate backbone in one strand of the double helix, leading to topological rearrangement of supercoiled DNA. Molecular dynamics (MD) simulation show that the stronger affinity for hydrogen‐bond formation and hydrophobic interaction between d ‐cysteine and DNA than that of l ‐cysteine is the origin of enantioselectivity. Abstract : Top mimics : Cysteine‐derived chiral carbon dots (CDs) can mimic topoisomerase I and thus mediate the enantioselective topological rearrangement of supercoiled DNA via cleaving one strand of DNA double helix. The gene expression of CD‐treated plasmid DNA is analogous to the regulation effect of topoisomerase I on gene expression.